Prescribing pattern of fixed dose combinations of antibiotics in a post-operative surgical ward of tertiary care teaching hospital - R., Velvizhy; J., Johan Pandian (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Fixed dose drug combinations (FDCs), are combinations of two or more active drugs. It should be used when the combination has an established advantage over single drug in efficacy, safety and compliance. The World Health Organization (WHO) lists only 19 of such combinations. But Indian market is filled with hundreds of FDCs which were not approved leading to irrational use. This study was focused on finding out the fixed dose combination of antimicrobial agents used in the post-operative general surgery ward of a tertiary care teaching hospital. Methods: After getting approval from institutional human ethics committee the prescriptions of patients admitted during April 2013 to March 2014 were analyzed. Demographic data, FDC prescribed by surgeons, Dose, Frequency, Duration, Route, Formulation, Brand or generic drugs, Adverse events due to use of FDC were collected and SPSS version 17 was used for statistical analysis. Fixed dose combinations were used in 90 Patients. The most commonly used FDC were ampicillin with Cloxacillin (43) followed by amoxicillin with clavulanic acid (22), cefoperazone with sulbactam (19) and piperacillin with tazobactam (6). A common drug used in combination along with FDC was metronidazole and aminoglycoside. The irrational combination seen in this study was ampicillin with Cloxacillin (8.88%) of the total FDC which is not approved by DCGI or FDA. Results: In this study out of 145 drugs used, 41drugs were administered three times a day, 90 drugs were given two times a day and 14 drugs were given once a day dosing. 53 patients received FDCs for prophylaxis and 37 patients for treatment purpose. All FDCs were prescribed in brand names. No adverse drug reaction was observed in this study. Conclusions: Consultants should undergo continuing medical education (CME) on newer drug combinations and their adverse drug reactions which will be evidence-based rather than to rely on representatives.